THE INFLUENCE OF Si/Al MOLE RATIO OF PRECURSOR SOLUTION ON THE STRUCTURAL PROPERTIES OF MCM-41 FROM FLY ASH - Sutarno Sutarno; Yateman Arryanto; Stefani Wigati (Indonesian Journal of Chemistry, 2003)
The synthesis of MCM-41 from fly ash was done hydrothermally at 100°C for 72 hours using supernatant of fly ash solution, sodium silicate, tetramethylammonium hydroxide (TMAOH) and cetyltrimethyl-ammonium hydroxide (CTMAOH) surfactants. The effect of Si/Al mole ratio of precursor solution on the structural properties of MCM-41 was studied by variation of the volume composition of supernatant and sodium silicate. The surfactant was removed by calcination at 550°C for 5 hours with heating rate 2°C/minute. The as-synthesized products were characterized by X-ray diffraction, infrared spectroscopy, and nitrogen adsorption methods. The XRD pattern proved that the samples were MCM-41 and the higher the Si/Al mole ratio of precursor solution resulted MCM-41 with higher crystallinity. Calcination was able to remove the CTMAOH surfactant. It was identified by the disappearance of the peak at 3000-2850 cm-1, which is characteristic for CTMAOH. The XRD pattern of calcined MCM-41 showed the decreaseof dspacing  and the increase of crystallinity. MCM-41 synthesized with Si/Al mole ratio of precursor solution=44.5 showed the highest crystallinity and has specific surface area=694.5 m2/g, average pore diameter=35Å and pore wall thickness=13.6Å.